ODL’S postmortem, students as customer or product? / Shakirah Mohd Saad ... [et al.] - Mohd Saad, Shakirah; Ahmad, Intan Nazrenee; Md Zani, Rosliza (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
The whole world is battling the pandemic, putting social distancing as the prevention measure to combat the COVID-19 pandemic. The education system has drastically adopted online distance learning (ODL) from the beginning of this pandemic in March 2020. ODL is the only alternative available for the education system to survive during the COVID-19 pandemic, thus, it is not an option. Educators and students have been forced to adopt ODL even though normally students would prefer face-to-face learning over online learning (Bunce et al., 2017). Due to the prevalence of COVID-19, ODL may be used for a substantial time, where attention for continuous improvement should be looked into or it will result in poor quality of education and distort the acquiring process of knowledge amongst students (Yekefallah et al., 2021).